Potensi Energi Terbarukan dari Limbah Sapi dan Enceng Gondok (Eichhornia crassipes) di Kutai Timur - Kurniawan, Benny; Amprin, Amprin; Marlena, Leni; Aryanto, Dhani (JURNAL GREEN HOUSE, 2025)
This study aims to analyze the potential of biogas production from a mixture of cow dung and water hyacinth (Eichhornia crassipes) as an alternative energy solution in East Kutai. The research applied an experimental method with four substrate composition treatments: P1 (85% cow dung : 15% water hyacinth), P2 (75%:25%), P3 (60%:40%), and P4 (100% cow dung). Each treatment was fermented for 20 days using laboratory-scale biodigesters, with daily monitoring of gas pressure and internal temperature. The results showed that P4 generated the highest biogas pressure (2.9 kPa), while increasing the proportion of water hyacinth reduced production efficiency. Fermentation temperatures remained stable within the mesophilic range (35–38°C), indicating ideal conditions for methanogenic microbes. MANOVA analysis confirmed that substrate composition significantly affected both pressure and temperature (p < 0.05). This study demonstrates that co-digestion of livestock and aquatic biomass waste can be an effective strategy for renewable energy production and organic waste management. The findings are applicable for the development of local-scale biogas technology in biomass-rich areas.